KEWENANGAN MAJELIS PERMUSYAWARATAN RAKYAT MENURUT UNDANG- UNDANG NOMOR 2 TAHUN 2018 TENTANG MPR, DPR, DPRD, DAN DPD - Poltak Siringoringo (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract Indonesia has experienced rapid development in the state administration system since the demands for reform were marked by the fall of Soeharto from power in May 1998. Reformation as a form of total correction of the practice of running a centralized state that occurred during the leadership of the Orde Baru Era. The hegemony of the power of the President during the Orde Baru Era placed other state organs in a weak position functionally, including the Indonesian People's Representative Assembly. Since the Soeharto regime ended there was a fairly fundamental ow of change in the life of the Indonesian state administration. In the Indonesian constitutional structure, the People's Consultative Assembly of the Republic of Indonesiais one of the important pillars of the people's representative institutions besides the House of Representatives and the Regional Representative Coun- cil Keywords:Orde Baru Era; Soeharto Regime; State Administration; Indonesian constitutional structure.